Sources and types of banana planting materials used by farmers in Uganda and Tanzania - Marimo, Pricilla; Kibooga, Charity (2020)
This report provides an overview of the types and sources of planting material used by 1315 farmers in Uganda and Tanzania. The data was collected from six dristricts; Luwero and Mbarara in Uganda and Meru, Moshi, Bukoba and Rungwe in Tanzania. Nearly all farmers who participated in the study used suckers which they obtained them from their own farms or from friends and neighbours. Suckers are more readily available, exchanged for free or affordable and accessible to farmers. The results highlight the limited uptake of other planting material types that are mostly provided by formal institutions as evidenced by the low numbers of farmers who indicated that they used tissue culture and macropropagated plantlets. Possible sources of tissue culture and macropropagated planting materials include research stations, private sector and non-governmental organizations, which were the least used sources. Nevertheless, 38 farmers (which is still a relatively low number) from Luwero district in Uganda reported that they used tissue culture plantlets which they mostly obtained from agricultural extension services. Results show that social ties and cultural norms influence banana planting material types and sources. There is very little diffusion and use of alternative source and types that are considered formal.